2023
DOI: 10.3389/fspor.2023.1086227
|View full text |Cite
|
Sign up to set email alerts
|

The effect of severe intensity bouts on muscle oxygen saturation responses in trained cyclists

Abstract: Near-infrared spectroscopy (NIRS) quantifies muscle oxygenation (SmO2) during exercise. Muscle oxygenation response to self-paced, severe-intensity cycling remains unclear. Observing SmO2 can provide cycling professionals with the ability to assess muscular response, helping optimize decision-making. We aimed to describe the effect of self-paced severe intensity bouts on SmO2, measured noninvasively by a wearable NIRS sensor on the vastus lateralis (VL) muscle, and examine its reliability. We hypothesized a gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…However, V̇O 2 measurement is extremely costly and requires highly skilled technicians to collect and interpret the data, ultimately limiting its broad utilization in simple clinical and sport testing facilities. Among the most promising alternative approaches for tracking muscle metabolic demands during exercise, near-infrared spectroscopy (NIRS) is of utmost interest since it provides noninvasive continuous monitoring of O 2 saturation in the microvasculature surrounding the active musculature ( 4 , 5 ). Recent evidence has suggested that NIRS is a valid tool for characterizing the dynamics of muscle O 2 changes (i.e., the balance between O 2 delivery and extraction by the skeletal muscles) among different exercise intensities ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, V̇O 2 measurement is extremely costly and requires highly skilled technicians to collect and interpret the data, ultimately limiting its broad utilization in simple clinical and sport testing facilities. Among the most promising alternative approaches for tracking muscle metabolic demands during exercise, near-infrared spectroscopy (NIRS) is of utmost interest since it provides noninvasive continuous monitoring of O 2 saturation in the microvasculature surrounding the active musculature ( 4 , 5 ). Recent evidence has suggested that NIRS is a valid tool for characterizing the dynamics of muscle O 2 changes (i.e., the balance between O 2 delivery and extraction by the skeletal muscles) among different exercise intensities ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the Moxy has been used in various studies in applied settings (e.g. Olcina et al 2019;Paquette et al 2021;Pratt 2018;Yogev et al 2023b), its reliability has not yet been adequately studied. In order to meaningfully implement the Moxy in training, reproducibility of SmO 2 , bilateral side differences and between-device measurement error need to be known.…”
Section: Introductionmentioning
confidence: 99%
“…This is vital for the decision if a change between two tests is "real" or due to measurement or biological error (Chrzanowski-Smith et al 2020). The validation study from Feldmann et al (2019) and a few others investigated the test-retest reliability during different activities such as rest, sitting, walking and endurance exercise (Contreras-Briceño et al 2019;Crum et al 2017;Gandia-Soriano et al 2022;McManus et al 2018;Scholkmann and Scherer-Vrana 2020;Yogev et al 2023bYogev et al , 2023a. Two of those studies looked at the test-retest reliability during cycling and came to different conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…When measuring local oxygen utilisation with the NIRS system, it is often used only on one leg—either on the dominant or non-dominant leg [ 13 , 14 ]. Recent studies [ 9 , 15 ] have introduced new findings regarding the importance of bilateral signal recording for a comprehensive understanding of the processes contributing to power output.…”
Section: Introductionmentioning
confidence: 99%